2005
DOI: 10.1503/cmaj.045156
|View full text |Cite
|
Sign up to set email alerts
|

Severe maternal morbidity in Canada, 1991-2001

Abstract: Background: Although death rates are often used to monitor the quality of health care, in industrialized countries maternal deaths have become rare. Severe maternal morbidity has therefore been proposed as a supplementary indicator for surveillance of the quality of maternity care. Our purpose in this study was to describe severe maternal morbidity in Canada over a 10-year period, among women with or without major pre-existing conditions. Methods: We carried out a retrospective cohort study of severe maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(151 citation statements)
references
References 11 publications
(17 reference statements)
5
141
3
2
Order By: Relevance
“…Our findings suggest that the association of older maternal age and obesity with increased odds of dying observed in the CMACE/UKOSS study 160 could be mediated to some extent through medical comorbidities. Unlike other studies, 25,153 we did not find pre-existing diabetes mellitus and cardiac conditions to be associated with maternal death. Whether or not this reflects improved obstetric care of women with diabetes and cardiac disease is unclear and requires further research.…”
Section: Conclusion and Implications For Policy And Practicecontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings suggest that the association of older maternal age and obesity with increased odds of dying observed in the CMACE/UKOSS study 160 could be mediated to some extent through medical comorbidities. Unlike other studies, 25,153 we did not find pre-existing diabetes mellitus and cardiac conditions to be associated with maternal death. Whether or not this reflects improved obstetric care of women with diabetes and cardiac disease is unclear and requires further research.…”
Section: Conclusion and Implications For Policy And Practicecontrasting
confidence: 99%
“…Studies in other developed countries have investigated near-miss maternal morbidity through routine sources of data, [22][23][24][25] but these studies are limited in their scope to identify risk factors by incomplete information on potential confounders. 26 In addition, the use of routine data means that these studies are unable to investigate diagnosis and management and hence provide evidence to improve clinical care.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have investigated severe acute maternal morbidity or 'near-miss' as a surrogate for evaluating obstetric care. [4][5][6][7] There is great variation in published studies in defining near-miss. 8,9 A 1-year prospective multi-center study defined 'near-miss' as an acute organ system dysfunction, which if not treated appropriately, could result in death.…”
Section: Introductionmentioning
confidence: 99%
“…13 Another large retrospective study estimated the incidence and predictors of severe obstetric morbidity, which was defined as severe pre-eclampsia, eclampsia, hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome, severe hemorrhage, severe sepsis and uterine rupture. 7 Geller et al 14,15 have proposed a scoring system to classify women with severe morbidity and nearmiss morbidity. These studies have suggested that the identification of risk factors for severe morbidity may improve maternal care.…”
Section: Introductionmentioning
confidence: 99%